Pengaruh Lamanya Jangka Waktu Audit dan Skeptisisme Profesional Auditor terhadap Kualitas Hasil Audit: Studi pada Auditor Inspektorat Aceh - Mislinawati Mislinawati (Jurnal Serambi Ekonomi dan Bisnis, 2017)
This research aims to explore the influence of the audit assignment duration and auditor's professional skepticism toward quality of audit result at the auditor inspectorate Aceh, both simultaneously and partially. The population of this research is the auditor inspectorate Aceh. This research applies a cencus method. The population of this study is 57 person. The analysis method used in this research is multiple regression analysis. The results of this research indicate that both simultaneously and partially, the audit assignment duration and auditor’s professional skepticism affect the quality of audit result.